Activation of tolvaptan-responsive T-cell clones with the structurally-related mozavaptan. (15th January 2023) - Hammond, Sean; Meng, Xiaoli; Mosedale, Merrie; Naisbitt, Dean J.
Abstract: Tolvaptan is an effective drug for the treatment of autosomal dominant polycystic kidney disease, but its use is associated with a significant risk of T-cell-mediated liver injury in a small number of patients. An important clinical conundrum following the contraindication of tolvaptan is whether administration of agents of similar pharmacological action and structure will be tolerated. Herein, we addressed this question through the exposure of tolvaptan-responsive T-cell clones to similar pharmaceutical agents. Whilst lixivaptan and conivaptan did not activate tolvaptan-responsive T-cells, mozavaptan evoked proliferative responses comparable with tolvaptan itself, indicating that there may be collateral immunological intolerance to this compound as a product of sensitization to tolvaptan. Graphical Abstract: ga1 Highlights: I n vitro assays show tolvaptan primed T-cells are cross-reactive to the structurally related drug Mozavaptan. No cross reactivity was seen to the parent compounds lixivaptan or conivaptan for tolvaptan (or metabolite) responsive T-cells. Data indicates the potential capacity of structurally related compounds to elicit T-cell responses in patients previously sensitised to tolvaptan. Further work is needed to determine the role of antigen cross-reactivity in the recently observed DILI in lixivaptan treated patients.